MEASUREMENT VALUE OF BANJAR ETHNIC MANDIBULAR INCISOR POSITION USING LATERAL CEPHALOMETRIC RADIOGRAPH - Nor Helma Warni; Didit Aspriyanto; Agung Satria Wardhana; Isyana Erlita; Ika Kusuma Wardani (Universitas Lambung Mangkurat, 2025)
ABSTRACTBackground: Appearance is one of the most important things for everyone in this modern era. Malocclusion, also known as tooth-jaw disharmony, can lead to a decline in a person's appearance. The position and inclination of the anterior teeth must be favorable to ensure maximum facial harmony. One common effort to achieve maximum facial harmony is orthodontic treatment. To support this treatment, x-rays are needed, one of which is the cephalometric technique with Steiner analysis. Purpose: This study aims to determine the measurement value of the mandibular incisor position of Banjarese students of SMAN 12 Banjarmasin from the lateral cephalometric radiograph using Steiner analysis. Method: Cephalometric measurements were carried out using the Steiner analysis method on the dental landmarks; L1-NB. Data analysis was carried out using descriptive statistical methods. The sample in this study was secondary data from previous research and took pure Banjarese students of SMAN 12 Banjarmasin, characterized by at least two generations (father, mother, grandfather, and grandmother) who had never or were not undergoing orthodontic treatment and were willing to be subjects in the study. Results: The average value of L1-NB distance measurement was 7.18±2.31 mm and the L1-NB inclination measurement was 30.22˚±6.16˚. Conclusion: The average value of mandibular incisor position in students of SMAN 12 Banjarmasin was classified as protrusion, and the average inclination was also included in the proclination group.Keywords: banjar ethnic, cephalometry, lateral cephalometry, steiner analysis ABSTRAK Latar belakang: Penampilan menjadi salah satu hal terpenting bagi setiap orang di era modern ini. Ketidakharmonisan relasi gigi dan rahang atau yang dikenal dengan maloklusi akan menyebabkan penurunan penampilan seseorang.Posisi dan kemiringan gigi anterior ini harus menguntungkan untuk memastikan keharmonisan wajah yang maksimal. Usaha yang biasa dilakukan untuk mendapatkan keharmonisan wajah yang maksimal salah satunya melakukan perawatan ortodonti.Untuk mendukung perawatan tersebut, perlu dilakukan rontgen salah satunya teknik sefalometri dengan analisis Steiner.Tujuan: Penelitian ini bertujuan untuk mengetahui nilai pengukuran posisi insisif mandibula siswa SMAN 12 Banjarmasin yang berasal dari etnis Banjar ditinjau dari radiografi sefalometri lateral dengan menggunakan analisis Steiner. Metode: Pengukuran sefalometri dilakukan dengan menggunakan metode analisis Steiner pada landmark gigi; L1-NB. Analisis data dilakukan dengan metode statistik deskriptif. Sampel dalam penelitian ini merupakan data sekunder penelitian terdahulu dan mengambil siswa SMAN 12 Banjarmasin suku Banjar murni yang ditandai dengan minimal dua generasi (ayah, ibu, kakek, dan nenek) yang tidak pernah atau tidak sedang melakukan perawatan orthodonti dan telah bersedia menjadi subjek dalam penelitian. Hasil: Nilai rata-rata pengukuran jarak L1-NB sebesar 7.18±2.31 mm dan nilai pengukuran inklinasi L1-NB sebesar 30.22˚±6.16˚. Kesimpulan: Nilai rata-rata posisi insisif mandibula pada siswa SMAN 12 Banjarmasin tergolong protrusi, dan rata-rata inklinasi nya juga termasuk dalam golongan proklinasi. Kata kunci: analisis steiner, sefalometri, sefalometri lateral, suku banjar.